PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2016-2021) - Zakiah, Zakiah; Mawardi, Wisnu; Hasanatina, Foza Hadyu (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Firms are trying to increase their values, as this would represent the public’s trust in those firms for the efforts that they have made. Based on the gap phenomenons and research gaps that have been explained in this research, there are inconsistencies found in the independent variables examined on the firm values. This is the reason why this research was conducted, with the purpose of examining how profitability, leverage, liquidity, and firm size influence firm value. The population in this research are manufacturing firms listed on the BEI during the 2016-2021 period. The research samples used were 19 firms with the total of 114 observations. The research is based on quantitative data that was processed using multiple linear regression analysis technique through the SPSS 26 application. The results of the research reveal that profitability and firm size have a significant positive impact on firm value. Moreover, leverage has significant negative impact on firm value. Meanwhile, liquidity has no significant impact on firm value.